1997
DOI: 10.1136/thx.52.1.28
|View full text |Cite
|
Sign up to set email alerts
|

Occupational asthma due to chrome and nickel electroplating

Abstract: Abstractchromate solution is helpful in making the specific diagnosis where doubt exists. Background -Exposure to chromium dur- (Thorax 1997;52:28-32) ing electroplating is a recognised though poorly characterised cause of occupational Keywords: occupational asthma, electroplating, asthma. The first series of such patients chrome, nickel, bronchial provocation testing. referred to a specialist occupational lung disease clinic is reported. Methods -The diagnosis of occupationalChromium is the major ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(52 citation statements)
references
References 13 publications
(2 reference statements)
1
47
0
1
Order By: Relevance
“…Ni is a major component of ambient air particulate matter (1,35) that is associated with inappropriate immune responses (35,36), airway hyperresponsiveness (7,37), and increased cardiopulmonary disease (1). Mechanisms of action for inhaled Ni that are independent of its antigenicity remain poorly defined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ni is a major component of ambient air particulate matter (1,35) that is associated with inappropriate immune responses (35,36), airway hyperresponsiveness (7,37), and increased cardiopulmonary disease (1). Mechanisms of action for inhaled Ni that are independent of its antigenicity remain poorly defined.…”
Section: Discussionmentioning
confidence: 99%
“…Ni is a common component of alloy metals and is used in electroplating, stainless steel, coins, and jewelry (4,6,7). Inhalation of Ni has been associated with lung and nasal cancers (5,(8)(9)(10), fibrosis, and various other cardiopulmonary diseases (1,5), including acute lung injury (4,11).…”
mentioning
confidence: 99%
“…Common asthmagens identifiable by this method include metals such as cadmium (224,225), chromium (226,229), cobalt (230)(231)(232)(233), and nickel (234)(235)(236)(237)(238)(239) compounds. This method is aided by knowledge of the chemicals present in the workplace and the reversal of symptoms upon removal from the workplace.…”
Section: Evaluating Human Exposure and Its Relationship To Asthmamentioning
confidence: 99%
“…Inhalation is the primary route of occupational exposure to metals [2]. The studies relating to occupational exposure to Ni during nickelplating process have shown that nasal toxicity [3], nickel dermatitis [4], allergic contact dermatitis and hand dermatitis [5][6][7], occupational asthma [8], mortality due to stomach cancer and lung cancer [9] and renal tubular dysfunction [10] have been observed in nickelplating workers. Exposure to Ni has been shown to result in an increased level of trypsin and a decreased level of carboxypeptidase B in the pancreatic tissue of animals [11].…”
Section: Introductionmentioning
confidence: 99%